Effectiveness of planned teaching program on knowledge regarding control of blood sugar level among type-2 diabetes mellitus patients - Nabi, Kahkashan (International Journal of Nursing Research, 2023)
The world is experiencing a rapid epidemiological transition with a rising burden of non-communicable diseases or chronic diseases. Lifestyle-related diseases like Diabetes Mellitus (DM) have emerged as a major public health problem. Diabetes mellitus is a chronic disease of lifelong duration, and its management requires a fundamental change in the patient's lifestyle. Aim: To assess the pretest and post-test knowledge scores and compare them after administration of planned teaching program and to associate the pre-test knowledge scores with selected demographic variables. Methods: Quantitative research approach with pre-experimental one group pre-test post-test design was used to assess the knowledge of Type-2 Diabetes Mellitus Patients. Purposive sampling technique was used to select 50 sample items. Data was collected using Structured Interview Schedule. The tool was validated by 11 experts. Reliability of the tool was established by using Karl Pearson’s correlation coefficient (“r” = 0.92) Results: p-value was calculated which showed a significant difference between the pre-test and post-test mean scores indicating that the planned Teaching Program was effective in increasing the knowledge scores. Association of the pre-test knowledge scores with selected demographic variables by chisquare test revealed significant as well as non-significant results. Conclusion: In the pre-test most of the study subjects had average knowledge while as in the post-test most of the subjects had excellent knowledge indicating that the Planned Teaching Program was effective in improving the knowledge scores.